It's Your Fault! The Influence of Roboldo, a Social Robot, on Human Guilt and Shame in an Interactive Game - Paradeda, Raul Benites; Alves, Alisson de Oliveira; Sousa, Carlos Eduardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This research investigates the ethical consequences of human interaction with Roboldo, a cost-effective emotional robot assembled using low-cost hardware. Grounded in theories such as Computers as Social Actors and Robots as Persuasive Agents, the study examines the influence of blame attribution for mistakes on participants' sense of guilt and shame, specifically within a memory card game. Participants filled out questionnaires pre- and post-interaction with Roboldo, evaluating their initial perceptions of the robot and their levels of guilt and shame under two distinct conditions: one where Roboldo faults the participant for its errors, and another where it faults its developer. The findings reveal no significant differences in levels of guilt and shame between conditions. Additionally, no substantial changes were observed in overall perceptions of the robot's friendliness or effectiveness. These results underscore the complexity of emotional responses in human-robot interactions and emphasize the importance of ethical considerations in robot design.